Predicting the fatigue life of the SAE 1045 steel using an empirical Weibull-based model associated to acoustic emission parameters - Mohammad, Mazian; Abdullah, Shahrum; Jamaludin, Nordin; Inayatullah, Othman (Elsevier, 2014)
This paper presents the capability of acoustic emission (AE) technique to predict the fatigue life of SAE 1045 carbon steel using a newly formulated statistical distribution. The specific AE parameters and the number of cycles to failure of the tested specimens were correlated using the Weibull distribution approach. The AE and strain signals were experimentally measured using the AE sensor and strain gauge respectively, with the sensors attached to the specimen during the cyclic test at several stress levels of constant amplitude loadings. The empirical model developed from the newly developed h–N curve, in correlation to the AE hits-number and cycles to failure, suggested that the AE technique has the potential to assess fatigue life for SAE 1045 carbon steel. Also, the validation results presented in the Weibull probability distribution technique are presented in the end of this paper.